Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.01807
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Surface Layer Protein SlpB Has Pleiotropic Effects in the Probiotic Propionibacterium freudenreichii CIRM-BIA 129

Abstract: Propionibacterium freudenreichii is a beneficial Gram-positive bacterium, traditionally used as a cheese-ripening starter, and currently considered as an emerging probiotic. As an example, the P. freudenreichii CIRM-BIA 129 strain recently revealed promising immunomodulatory properties. Its consumption accordingly exerts healing effects in different animal models of colitis, suggesting a potent role in the context of inflammatory bowel diseases. This anti-inflammatory effect depends on surface layer proteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The extraction of such proteins suppresses P. freudenreichii immunomodulation (Le Marechal et al, 2015). The mutation of slpB, encoding one of these surface proteins, suppresses immunomodulation (Deutsch et al, 2017) as well as adhesion to host cells (do Carmo et al, 2017), and has many pleiotropic effects on the surface properties of P. freudenreichii (do Carmo et al, 2018b). In the present study, the expression of P. freudenreichii surface extractable proteins ( Figure 5 and Table 1), including SlpB and SlpA, suggested that interactions with host cells might be modified, with reduced adhesion to host cells (do Carmo et al, 2017) and unpredictable immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of such proteins suppresses P. freudenreichii immunomodulation (Le Marechal et al, 2015). The mutation of slpB, encoding one of these surface proteins, suppresses immunomodulation (Deutsch et al, 2017) as well as adhesion to host cells (do Carmo et al, 2017), and has many pleiotropic effects on the surface properties of P. freudenreichii (do Carmo et al, 2018b). In the present study, the expression of P. freudenreichii surface extractable proteins ( Figure 5 and Table 1), including SlpB and SlpA, suggested that interactions with host cells might be modified, with reduced adhesion to host cells (do Carmo et al, 2017) and unpredictable immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…This ability, which is highly straindependent (Foligné et al, 2013), is mediated by key extractable surface proteins (Le Marechal et al, 2015;Deutsch et al, 2017;Ge et al, 2020). Indeed, mutational inactivation of the slpB gene was recently shown to affect P. freudenreichii surface properties, as well as its anti-inflammatory role, both in vitro and in vivo (do Carmo et al, 2017(do Carmo et al, , 2018b(do Carmo et al, , 2019. Accordingly, the SlpB protein purified from P. freudenreichii was shown to mitigate inflammation in human intestinal epithelial cells (do Carmo et al, 2017;Rabah et al, 2018a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Results evidenced the involvement of SlpB and SlpE in the release of IL10 by human immune cells and demonstrated that different combinations of surface and cytoplasmic proteins, depending on the strain, exerted a pleiotropic effect on the anti-inflammatory properties (47). Finally, do Carmo et al demonstrated a direct role of SlpB in the adhesion to HT-29 cells and reported that the inactivation of slpB gene caused profound modifications in whole cell and surface proteomes as well as bacterial stress tolerance (81, 82).…”
Section: Proteomics For Studying Surface-exposed Proteins In Probioticsmentioning
confidence: 99%
“…In the case of P. freudenreichii, the adhesion of some strains to pig ileum cells (IPEC-J2) was between 25 and 35%, and that proportion was higher with the addition of CaCl 2 [51]. In the case of human host, several bacterial strains were tested for adhesion to HT-29 colon cells in vitro; the most adhesive strain was P. freudenreichii CIRM-BIA129 and surface layer protein B (slpB) key role in adhesion was demonstrated by using gene inactivation [52,53]. Another study demonstrated that bacterial adhesion to immobilized mucus could be synergistically improved by administration of strains combinations, such as P. freudenreichii ssp.…”
Section: Adhesion Propertiesmentioning
confidence: 99%
“…The multi-strain and multi-omics study conducted by Deutsch et al [77] clarified that cytoplasmic proteins might also be relevant in immunomodulation, but confirmed the key role of surface-layer proteins B (SlpB) and E (SlpE), particularly in strain P. freudenreichii CIRM-BIA129. SlpB was then shown to be crucial for bacterial adhesion to epithelial intestinal cells [52], and a mutation in its gene had pleiotropic effects, suggesting this protein could have a central role in cellular processes [53]. Additionally, in vivo assays that were conducted in mice with mucositis induced by 5-Flourouracil (5-FU), showed that SlpB protein is crucial for the cytokine modulation triggered by P. freudenreichii CIRM-BIA129 [83].…”
Section: Immunomodulatory Propertiesmentioning
confidence: 99%